2001
DOI: 10.1023/a:1013070612986
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pharmacokinetic data of a docetaxel-epirubicin combination in metastatic breast cancer

Abstract: In order to explore activity and pharmacokinetic data of a docetaxel-epirubicin combination we analyzed a population of 60 metastatic breast cancer patients. All the patients had an ECOG performance status < 3; 41 patients (68%) had visceral metastases as dominant site of disease, including 33% with liver metastases. Three or more involved organs were present in 43% of patients; 35% had received prior hormonotherapy; 10% for metastatic disease. Twenty-five patients (42%) had received prior adjuvant chemotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…From previous trials, we have found fewer adverse reactions with docetaxel and capecitabine compared with anthracycline or paclitaxel [7], [24], [25]. To some extent, addition of capecitabine did not significantly increase the toxicity, except for diarrhea and hand–foot syndrome related to capecitabine, but it might have reduced neutropenia and febrile neutropenia, which could have been due to reduced dose of docetaxel [3].…”
Section: Discussionmentioning
confidence: 78%
“…From previous trials, we have found fewer adverse reactions with docetaxel and capecitabine compared with anthracycline or paclitaxel [7], [24], [25]. To some extent, addition of capecitabine did not significantly increase the toxicity, except for diarrhea and hand–foot syndrome related to capecitabine, but it might have reduced neutropenia and febrile neutropenia, which could have been due to reduced dose of docetaxel [3].…”
Section: Discussionmentioning
confidence: 78%
“…Docetaxel was administered at the maximum accepted dose according to pharmacokinetic studies. 21,22 Therefore, this study seems to provide the best results that can be obtained in terms of dose-response effect. In addition, dose escalation of epirubicin could possibly increase the risk of cardiotoxicity.…”
Section: Discussionmentioning
confidence: 87%
“…Overall response rates of 57 -79% were reported with 3-weekly combinations of docetaxel 60 -80 mg m À2 in five first-line noncomparative studies in a total of 170 patients with metastatic breast cancer (Sparano et al, 2000;Baltali et al, 2001;Lippe et al, 2002;Aihara et al, 2003;Morales et al, 2004). Previous noncomparative studies of 3-weekly epirubicin 75 mg m À2 plus docetaxel 75 mg m À2 have yielded overall tumour response rates of 67 -84%, with overall survival of up to approximately 2 years (Airoldi et al, 2001;Yeo et al, 2002;Morales et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Haematologic adverse events (most notably neutropenia) were most common, with no excessive cardiac toxicity or any indication that the addition of docetaxel to doxorubicin increases the cardiotoxicity of the latter (Sparano et al, 2000;Baltali et al, 2001;Lippe et al, 2002;Aihara et al, 2003;Morales et al, 2004). In one phase II noncomparative trial of epirubicin and docetaxel, no grade 4 nonhaematologic adverse events and very low levels of cardiotoxicity (reversible congestive heart failure in one of 60 patients only) were observed (Yeo et al, 2002), whereas in another study there was no grade 3 -4 cardiac toxicity and no treatment-related mortality among 46 patients (Airoldi et al, 2001). A further recent trial of 133 patients reported that two withdrew treatment due to cardiotoxicity, although none developed congestive heart failure (Morales et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation